Minimally Processed Avocado Through Flash Vacuum‐Expansion: Its Effect in Major Physicochemical Aspects of the Puree and Stability on Storage. Issue 3 (7th July 2016) - Vargas‐Ortiz, Manuel; Rodríguez‐Jimenes, Guadalupe; Salgado‐Cervantes, Marco; Pallet, Dominique
Abstract: Industrial products avocado‐based include guacamole, pasta, frozen portions and crude oil. The pulp is susceptible to browning reactions and deterioration. Several technologies have been developed to control browning. A technology that could reduce the browning is the method of flash vacuum‐expansion. In this process the plant material is heated by steam and then is introduced into a vacuum chamber where occurs disintegration due to their instantaneous vaporization of part of the water constituent. The objective of this research is to evaluate the effect of the processing times of flash vacuum‐expansion method on changes during refrigerated storage (5C) of physical characteristics (color and brightness) and biochemical (titratable acidity, pH, polyphenoloxidase activity and total phenols) of avocado puree. The color (102–106 °Hue) and luminosity ( L = 56–60) of the puree are stable for at least 15 days. Modifies the initial pH (6.7–6.4). Polyphenoloxidase is inhibited and phenolic compounds increased. Practical Applications: The avocado fruit is very difficult to industrialize as the enzymatic browning is severe in the pulp problem, we consider that this research can explore application of a nontraditional technology that seems to be a good alternative since it avoids changing color and allows storage of the pulp without the addition of chemicals. Therefore, we believe that the results obtained in this research are of great interest to the food industry since many fruits are affected by the enzymatic browning and ever increasing need to conserve the edible part of highly perishable fruits like avocado. The avocado fruit is a matrix that provides great challenges for industrialization because much of its protein content are enzymes besides being a fruit with a high lipid content, typically chemicals are applied to solve the problems that this generates; however, it is necessary to find methods that reduce the use of these chemicals. The avocado puree obtained by flash vacuum‐expansion presents physicochemical characteristics (color and phenolic content) which give a good quality without the addition of chemical additives; the results obtained in this research are of great interest to the food industry since many fruits are affected by the enzymatic browning and ever increasing need to conserve the edible part of highly perishable fruits like avocado. Theoretically, it can also reduce the microbial load of the products.